'It just opens up their world': autism, empathy, and the therapeutic effects of equine interactions. Issue 2 (4th May 2018) - Malcolm, Roslyn; Ecks, Stefan; Pickersgill, Martyn
ABSTRACT: Experiences of autism-spectrum disorder are now increasingly studied by social scientists. Human–animal relations have also become a major focus of social inquiry in recent years. Examining horse-assisted therapy for autistic spectrum disorders, this is the first paper that brings these fields together. Drawing on participant observation and interviews at a UK horse therapy Centre, this article examines how staff and the parents of riders account for the successes and limitations of equine therapy. To the respondents, horses 'open up' autistic children and make possible interactions that seemed impossible before. Horses were regarded as facilitating the emergence of apparently social behaviours, which included eye contact, pointing, and speech. Three key explanations emerged for therapeutic success: the sensorial, embodied experience of riding the horse; the specific movements and rhythms of the horse; and, the 'personality' of the horse. Equine therapy can be regarded as enabling a form of multispecies intersubjectivity, with the resonance between rider and horse seeming to make possible a new attunement between humans. Practices of equine therapy, and perceptions of its efficacy, serve in turn to attune social scientists to a version of empathy constituted through lively and sensorial interactions, as opposed to one that is restricted to particular kinds of humans.